Analisis Kinerja Parkir Dengan Metode Pembayaran QRIS Terhadap Retribusi Parkir Pada Peningkatan Pendapatan Asli Daerah Taman Bungkul Kota Surabaya - Faldy Putra Dharma; Kurnia Hadi Putra; Ratih Sekartadji; Theresia Maria (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Bungkul Park in Surabaya is a public space with high community activity that increases parking demand. The high number of vehicles and the presence of cash parking practices without official tickets may lead to revenue leakage in local parking retribution. The study aims to analyze parking characteristics and evaluate the potential implemantation of the Quick Response Code Indonesian Standard (QRIS) non-cash payment system to increase parking retribution revenue in the Bungkul Park area. This research used a quantitative method through field surveys to obtain data on parking volume, parking accumulation, parkng duration, parking capacity, and parking turnover rate. The results show that parking activity in Bungkul Park is relatively high, especially on weekends. The average parking duration ranges from 3,75 to 3,79 hours, with weekday parking volumes of 177 motorcycles and 111 cars, while weekend volumes increase to 319 motorcyles and 84 cars. The potential parking reribution revenue is estimated at Rp. 719.232.500 per years using fixed tarif system and can increase to Rp. 753.360.000 year with a progressive tariff system. The implementation of QRIS based non-cash payments is expacted to improve transaction transparancy and minimize parking revenue leakage, thereby supporting the increase of Surabaya’s Regional Original Revenue (PAD).